De la campagne à la ville : échanges, exploitation et immigration dans le Maghreb médiéval - Tariq Madani (Revue des Mondes Musulmans et de la Méditerranée, 2009)
The relation between Maghribi cities and their hinterland has yet to be explored in depth. Insufficient archives and the lack of archaeological approaches are slowing down the understanding of the various manifestations of this issue. Without being aware of the economic, social, and cultural phenomena of the countryside, it is not yet possible to ask fundamental historical questions. A theoretical and historical contextualization shows diverse cases and complex relations that are not unilateral between Islamic cities and their hinterland. In other words, one cannot reach reliable conclusions concerning global or regional history without putting together, across centuries, exploitative relations along with interdependency within a division of labor and resources that link the city with its environment. Marketing agricultural produces and products in the city, the natural function of an outlet for rural population, the function of a judicial and administrative center, and the function of a locus for acculturation of multiple ethnic groups, are aspects less conflictual of these relations that should be included in discussion, in order to recapture them at the stage of a synthesis.